Comparison of in situ sediment remediation amendments: Risk perspectives from species sensitivity distribution. (1st March 2021) - Albarano, L.; Lofrano, G.; Costantini, M.; Zupo, V.; Carraturo, F.; Guida, M.; Libralato, G.
Abstract: Contaminated sediment is a major issue for aquatic environments, but attention must be kept even during remediation activities that can negatively affect resident biota especially when applied in situ . For the first time, the species sensitivity distribution (SSD) approach was applied to amendments used for in situ sediment remediation considering 39 papers including both freshwater (F) and saltwater (S) effect data (i.e. n = 17 only F, n = 19 only S, and n = 3 both F and S). Toxicity data related to the application of activated carbon (AC), nano-Zero-Valent-Iron (nZVI), apatite (A), organoclay (OC) and zeolite (Z) were collected and analyzed. SSD curves were constructed by lognormal model providing comprehensive comparisons of the sensitivities of different species to the relative testing methods. Results indicated that Bacteria were the most sensitive group of testing organisms, while Crustaceans were the less sensitive. The hazardous concentration for 5% of the affected species (HC5) were derived to determine the concentration protecting 95% of the species. OC, A and Z presented both acute and chronic toxicity. The HC5 values in descending order are: AC (4.79 g/L) > nZVI (0.02 g/L) > OC, A and Z (1.77E-04 g/L). AC and nZVI can be considered safer than OC, A and Z in sediment remediation activities, even if in situ long-term effects remained still underexplored. Graphical abstract: Image 1 Highlights: SSD evidenced that AC, nZVI and OC, A and Z present a species-specific sensitivity effect. Bacteria are the most sensitivity group. AC and nZVI are safer than OC, A, and Z in in situ contaminated sediment remediation activities. Abstract : Capsule: In situ sediment remediation amendments were compared considering a species sensitivity distribution approach evidencing that AC and nZVI are the most suitable for the specific purpose.